Developing lifelong learning skills for entrepreneurial competences among the indigenous Kensiu community in Malaysia - Christopher, Anne Althea; Dzakiria, Hisham (WOJDE, 2014)
Globally, indigenous peoples throughout the world have sustained their unique world views and associated knowledge systems for millennia. Despite advancement and development a country has achieved, the indigenous people are always found to be left behind from the mainstream of development facing educational and economic issues.This paper presents findings from a research project conducted by Enactus (Entrepreneurs in Action) Universiti Utara Malaysia to support lifelong learning, and as an enabler to inculcate entrepreneurial skills among selected indigenuous community in Malaysia. Known for its successful programs, Enactus, a non-profit global organization mobilizes university students to create community empowerment projects.This project essentially aims to improve the standard of living of disadvantaged communities in Malaysia.This indigenous community known as the Kensiu in the rural villages of Lubuk Legong in Baling was targeted for the project as they faced a lot of problems and challenges ranging from economic problems, hygiene problems and social problems to lack of knowledge.The project was carried out to help develop the lower level skills of the Kensiu community with a focus on educating them on how to carry out their own business. Findings shows with adequate exposure, skills, and integrated efforts from all stakeholders, indigenous people can become great learning communities with much potential for economic and educational success.